Green Biomass Pretreatment for Biofuels Production - Gu, Tingyue; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
The increasing global demand for energy requires a versatile approach, prompting many researchers to focus on renewable bioenergy from different biomasses, especially cellulosic biomass. Such biomasses can be agricultural wastes, municipal wastes or direct harvests from high-yield energy corps. If properly pre-treated, the subsequent enzyme hydrolysis step is much more effective and can effectively minimises the waste disposal. Green Biomass Pretreatment for Biofuels Production reviews a range of pretreatment methods such as ammonium fiber explosion, steam explosion, dilute acid hydrolysis, alkali hydrolysis, and supercritical carbon dioxide explosion focusing on their final sugar yields from hemicellulose, glucose yields from cellulose, as well as on their feasibilities in bioenergy production processes at various scales. This book emphasises the tactical mobile and on-farm scales applications that use green pretreatments and processing technologies without the need of on-site waste treatment. Because of the varieties of different biomasses, no single pretreatment is expected to be the universal choice. Some of the pretreatment methods present niche applications are also discussed.
(3z(BPlant Cell Wall Structure-Pretreatment(3y (Bthe Critical Relationship in Biomass Conversion to Fermentable Sugars -- Thermo-Mechanical Pretreatment of Feedstocks -- Solid-State Biological Pretreatment of Lignocellulosic Biomass -- Hydrothermal Pretreatment of Lignocellulosic Biomass -- Pretreatment of Lignocellulosic Biomass Using Supercritical Carbon Dioxide As A Green Solvent -- Pretreatment of Lignocellulosic Biomass Using Green Ionic Liquids.s
Keywords: Engineering; Chemical engineering; Renewable energy sources; Surfaces (Physics).; Engineering; Industrial Chemistry/Chemical Engineering; Renewable and Green Energy; Renewable and Green Energy; Characterization and Evaluation of Materials; Applied and Technical Physics; Applied and Technical Physics